Effects of haloperidol inhalation on MK-801- and memantine-induced locomotion in mice. Issue 1 (1st January 2020) - Ueno, Hiroshi; Suemitsu, Shunsuke; Murakami, Shinji; Kitamura, Naoya; Wani, Kenta; Takahashi, Yu; Matsumoto, Yosuke; Okamoto, Motoi; Ishihara, Takeshi
ABSTRACT: The administration of therapeutic agents is difficult in many patients, such as patients with post-operative delirium or dementia or patients with schizophrenia, who are upset in an emergency room. Therefore, the development of a new method for administering therapeutic agents to the central nervous system is desired. In this study, we investigated if inhalation was an effective route of administration for haloperidol, a commonly used, strong antipsychotic. Dizocilpine, also known as MK-801, is a noncompetitive antagonist of the N-methyl-D-aspartate receptor. MK-801 or memantine-induced motor hyperactivity was evaluated in mice following either intraperitoneal injection or inhalation of haloperidol or the histamine neuroactivator betahistine. Pretreatment with haloperidol inhalation inhibited the MK-801-induced or memantine-induced increase in locomotor activity. This effect was similar to that of the intraperitoneal administration of haloperidol. However, pretreatment with inhaled betahistine or the intraperitoneal administration of betahistine did not suppress the MK-801-induced or memantine-induced increase in locomotor activity. Thus, haloperidol when inhaled acts on the central nervous system of mice and suppresses the MK-801-induced increase in mouse locomotor activity. Our findings suggest that inhalation may be a novel method for administering haloperidol. Abbreviations: ANOVA: analysis of variance